Pentingnya Memahami Pertumbuhan dan Perkembangan Peserta Didik Sekolah Dasar untuk Memaksimalkan Pembelajaran - Ermayanti, Wita; Handayani, Arri; Rakhmawati, Dini (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
This article was created with the aim of providing knowledge to readers about the importance of understanding the factors that influence the growth and development of elementary school students in maximizing learning. This article was written using the library study method, by examining various sources or references such as books and several other journals that are relevant to the topic being studied. The results and discussion explain that understanding student development can help teachers choose the best learning environment and get to know their students' personalities better. Thus, with the teacher's understanding of the growth and development of students, it can provide an overview of appropriate learning procedures to maximize learning and foster feelings of comfort in studying at school.